Prediksi Kualitas Minuman Anggur Putih Berdasarkan pH dan Alkohol Yang Terkandung Didalamnya Menggunakan Metode KNN - Ahmad Muhajjir Ridwan (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2026)
This study aims to develop a white wine quality prediction model using two main parameters, namely pH and alcohol content. The quality of white wine is often influenced by the balance between acidity (pH) and alcohol content, which can affect the flavor, aroma and freshness of the final product. In this study, white wine sample data that included variations in pH and alcohol content were analyzed to determine the correlation between these two parameters and the perceived quality determined by panelists. The K-Nearest Neighbor method was used to build a prediction model that could estimate wine quality based on pH and alcohol values. The results showed that pH and alcohol content have a significant relationship to white wine quality, with lower pH and certain alcohol levels contributing to improved wine quality. The developed model can be used by wine producers to control and improve the quality of their products, as well as provide a basis for further research into other factors affecting wine quality.